Appendiceal Neuroendocrine Tumor Mimicking Acute Appendicitis - Gautam, N.; Makaju, R.; Basnet, D.; Lama, B.; Maharjan, P. B.; Dahal, S. (Kathmandu University Medical Journal, 2022)
Appendiceal carcinoids are the most frequent tumors arising from the appendix, comprising between 32 and 57% of all the appendiceal tumors. The gross appearance of the appendix showed perforation at the tip with 30 ml of peri-appendicular collection. On histopathological examination, carcinoid tumor on the tip of appendix was found with tumor cells arranged in tubules, acini and nests infiltrating the muscularis propria and sub serosa. Perineural and vascular invasion was not seen. Immunohistochemistry for Synaptophysin was positive with Ki-67 labelling index of 2%. We present a case of appendiceal neuroendocrine tumor with the chief complaint of acute appendicitis.